2015
DOI: 10.1007/s11064-015-1681-3
|View full text |Cite
|
Sign up to set email alerts
|

Battling Alzheimer’s Disease: Targeting SUMOylation-Mediated Pathways

Abstract: SUMO (small ubiquitin-like modifier) conjugation is a critically important control process in all eukaryotic cells, because it acts as a biochemical switch and regulates the function of hundreds of proteins in many different pathways. Although the diverse functional consequences and molecular targets of SUMOylation remain largely unknown, SUMOylation is becoming increasingly implicated in the pathophysiology of Alzheimer's disease (AD). Apart from the central SUMO-modified disease-associated proteins, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 101 publications
(113 reference statements)
0
17
0
Order By: Relevance
“…However, constitutively increased sumoylation has rather negative effects and correlates with resistance to cancer treatments, increased tumor metastasis and relapse (20)(21)(22)(23)(24). Also, several other diseases, like neurological disorders, diabetes and heart failure, were connected to defects in the SUMO system (25)(26)(27)(28). Together, these findings point to an important role of sumoylation in maintaining cell homeostasis and it is of key importance to understand its substrate specificity and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, constitutively increased sumoylation has rather negative effects and correlates with resistance to cancer treatments, increased tumor metastasis and relapse (20)(21)(22)(23)(24). Also, several other diseases, like neurological disorders, diabetes and heart failure, were connected to defects in the SUMO system (25)(26)(27)(28). Together, these findings point to an important role of sumoylation in maintaining cell homeostasis and it is of key importance to understand its substrate specificity and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs through the regulation of some of the most fundamental metabolic processes, including energy and nucleotide metabolism, and permits physiological adaptation in response to cellular and environmental queues (Enserink 2015; Makhnevych et al 2009). SUMO has been implicated in complex human diseases and developmental anomalies that are also associated with nutritional and/or metabolic perturbations including Alzheimer’s disease (Dorval and Fraser 2007; Hoppe et al 2015; Lee et al 2013, 2014b; Martins et al 2016; McMillan et al 2011; Sarge and Park-Sarge 2009), Parkinson’s disease (Guerra de Souza et al 2016) (Eckermann 2013; Krumova et al 2011), type I diabetes (Li et al 2005; Wang and She 2008), familial partial lipodystrophy (Simon et al 2013), diabetes-mediated cardiovascular disease (Chang and Abe 2016), congenital heart disease (Wang et al 2011), cardiomyopathy (Kim et al 2015c; Zhang and Sarge 2008), arthritis (Yan et al 2010), amyotrophic lateral sclerosis (Dangoumau et al 2016; Foran et al 2013; Niikura et al 2014), and cleft lip and/or palate (Alkuraya et al 2006; Song et al 2008; Tang et al 2014). …”
Section: 1 Introduction: Functions Of Sumo In Metabolismmentioning
confidence: 99%
“…Furthermore, we found that the localization of SUMO1 conjugates remains unchanged during aging and AD pathology and that SUMO1 conjugates are not found in amyloid plaques. Therefore, it appears unlikely that alterations in the SUMO1 conjugation equilibrium contribute significantly to any toxic or neuroprotective processes related to AD (Martins et al., 2016). However, as the level of SUMOylated RanGAP1 did not decrease during aging as seen for global SUMO1 conjugation, we cannot exclude the possibility that subtle changes involved in aging or AD progression can occur at the level of individual (especially nuclear) SUMO1 substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, SUMOylation can regulate the solubility of various disease‐associated proteins (Krumova & Weishaupt, 2013; Lee et al., 2013; Shahpasandzadeh et al., 2014). Furthermore, altered SUMOylation—at the global level of SUMOylated proteins or with regard to the SUMOylation status of specific disease‐related proteins—has been reported in the context of a large variety of neurological disorders with altered proteostasis, including AD as the most common age‐related neurological disorder (Lee et al., 2013; Martins, Tasca & Cimarosti, 2016). Indeed, several AD‐related proteins (such as α‐synuclein, tau, and APP) have been proposed to be SUMO1 conjugates (Martins et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation